Anthropometric characteristics, body composition and somatotyping of high and low performer shot putters - Singh, K.; Singh, P.; Singh, C. (International Journal of Sports Science and Engineering, 2012)
The purpose of this study was to find out anthropometric measurements, body composition and somatotyping differences in high performer and low performer shot putters. 20 male shot putters of age 18 to 25 years were assessed for the present study. Out of which 10 were high performers and 10 were low performers. All subjects were assessed for height, weight, widths, girths and skinfold thickness. The independent samples t-test revealed that high performer shot putters were significantly taller (p<0.01) and had significantly greater all the length measurements when compared to low performer shot putters. The high performer shot putters also possessed significantly greater upper arm (p<0.05), forearm (p<0.01), chest (p<0.05), thigh (p<0.05) circumferences and bi-humerus (p<0.01), wrist (p<0.05), bi-acromial (p<0.01), hip (p<0.05) diameters as compared to low performer shot putters. Endomorphy (p<0.05) was significantly higher in low performers while the lean body mass (p<0.05) was significantly greater in high performer shot putters. It is concluded that in most of the parameters there were significant differences between high performer shot putters and low performer shot putters, and the high performer athletes showed better anthropometric measurements and somatotyping scores.